2005
DOI: 10.1109/tnn.2005.853426
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Basis Selection: New Results and Application to Adaptive Prediction of Video Source Traffic

Abstract: Abstract-Real-time prediction of video source traffic is an important step in many network management tasks such as dynamic bandwidth allocation and end-to-end quality-of-service (QoS) control strategies. In this paper, an adaptive prediction model for MPEG-coded traffic is developed. A novel technology is used, first developed in the signal processing community, called sparse basis selection. It is based on selecting a small subset of inputs (basis) from among a large dictionary of possible inputs. A new spar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Because of its powerful learning and multi mapping ability, the neural network can construct a nonlinear model with the input and output data. It can accurately describe the nonlinear relationship among various factors, so it is widely used in network traffic prediction (Atiya, Alym, & Parlosa, 2005;Hou & Wu, 2015;Hussein, 2001;Yu, 2013;Zhao, 2013). But in practical applications, the neural network has some inevitable defects, such as slow convergence speed, the potential of local extreme points and the poor ability to adapt to the network, especially the initial weights and thresholds of the neural network have a great influence on the performance of (Li & Li, 2011).…”
Section: And Auto Regressive Integrated Movingmentioning
confidence: 99%
“…Because of its powerful learning and multi mapping ability, the neural network can construct a nonlinear model with the input and output data. It can accurately describe the nonlinear relationship among various factors, so it is widely used in network traffic prediction (Atiya, Alym, & Parlosa, 2005;Hou & Wu, 2015;Hussein, 2001;Yu, 2013;Zhao, 2013). But in practical applications, the neural network has some inevitable defects, such as slow convergence speed, the potential of local extreme points and the poor ability to adapt to the network, especially the initial weights and thresholds of the neural network have a great influence on the performance of (Li & Li, 2011).…”
Section: And Auto Regressive Integrated Movingmentioning
confidence: 99%
“…In this work, we apply the recursive linear regression model developed in [28] for estimating the demand curve parameters after acquiring each new price and its corresponding demand. We adopt the recursive linear regression model because it fits the recursive nature of the problem in case of considering multiple future time steps, where each time step updates and improves over the previous time step.…”
Section: Introductionmentioning
confidence: 99%
“…Several neuro-computational structures have been utilised for bandwidth prediction, for example: multilayer perceptron [19][20][21][22], radial basis function network [23], time-lagged feed-forward neural network [24], recurrent neural network [25,26] and neuro-fuzzy network [27]. In [21], the performances of different neural networks and normalised LMS (NLMS) predictor were compared and it was shown that the recurrent Elman network has better performance than the others in terms of root mean square error.…”
Section: Introductionmentioning
confidence: 99%